A contemporary assessment of polybrominated diphenyl ethers (PBDE) in the ambient air and soil of Azerbaijan - Aliyeva, Gulchohra; Sinnott-Clark, Carrie Amber; Audy, Ondřej; Škrdlíková, Lenka; Kukučka, Petr; Klánová, Jana; Halsall, Crispin (Environmental science and pollution research international, 2018)
PBDEs were measured in air and soil across Azerbaijan to establish contemporary concentrations at 13 urban and rural sites. Polyurethane foam passive air samplers (PUF-PAS) were deployed for a period of a month with surface soil samples collected at the same sites. Unlike organochlorine pesticides previously surveyed by our group, PBDE concentrations in both contemporary air and soil were low in comparison to recent European and Asian studies. For example, mean ∑9PBDE concentrations in air and soil were 7.13 ± 1.66 pg m-3 and 168 ± 57 pg g-1, respectively. The fully brominated BDE-209 was the most abundant congener observed in soil (174.8 ± 58.5 pg g-1), comprising ~ 96% of ∑10PBDE. However, the PAS-derived air concentrations for highly brominated congeners must be viewed with caution as there is uncertainty over the uptake rates of particle-bound chemicals using these devices. Some of the highest concentrations in air were observed at sites with the highest wind speeds and at several remote locations in the north of the country and this requires further research. Levels of BDE-47 and 99 (the two most abundant congeners in the widely used penta-formulation) were lower than levels reported elsewhere suggesting limited use/import of the penta-BDE formulation in Azerbaijan.
Keywords: Passive air sampler; halogenované difenylethery; pesticidy; Distribution; Polyurethanes; Environmental Monitoring; Soil Pollutants; látky znečišťující půdu; Halogenated Diphenyl Ethers; půda; Sources; Air Pollutants; Ázerbájdžán; Pesticides; Flame retardants; látky znečišťující vzduch; monitorování životního prostředí; polyurethany; Soil; Azerbaijan